Correction: Highly penetrative liposome nanomedicine generated by a biomimetic strategy for enhanced cancer chemotherapy. (13th May 2021) - Jia, Yali; Sheng, Zonghai; Hu, Dehong; Yan, Fei; Zhu, Mingting; Gao, Guanhui; Wang, Pan; Liu, Xin; Wang, Xiaobing; Zheng, Hairong
Abstract : Correction for 'Highly penetrative liposome nanomedicine generated by a biomimetic strategy for enhanced cancer chemotherapy' by Yali Jia et al., Biomater. Sci., 2018, 6, 1546–1555, DOI: ; 10.1039/C8BM00256H .